Pengaruh Infrastruktur Teknologi Informasi dan Akses Internet terhadap Kinerja Sistem Pembelajaran Daring Menggunakan Analisis Regresi Panel Data - Sri Mardiyati; Ulfa Pauziah; Nini Adelina Tanamal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the influence of information technology infrastructure and internet access on the performance of online learning systems in educational institutions in Indonesia. A quantitative approach was applied using panel data from 10 educational institutions during 2019–2023. Panel model selection indicates that the best model is Pooled OLS, based on the Chow and Lagrange Multiplier (LM) tests. The results show that information technology infrastructure has a positive and significant effect on online learning performance. Internet access also exhibits a positive and significant influence and becomes the most dominant factor supporting the success of digital learning. Simultaneously, both variables significantly affect online learning performance. This study highlights the importance of investing in IT infrastructure and improving internet quality to optimize digital learning implementation in educational institutions.